Vulnerabilidade e percepção de risco de acidentes com barragens de caulim em Barcarena. - AVELAR, Marcio dos Santos (Universidade Federal do Pará, 2019)
The society uses the existing natural resources and generates modifications in the nature with constructions of artificial structures such as the dams. Like other anthropogenic interventions, the construction of dams can bring diverse social benefits, from the generation of electric power, regulation of the flow for the purpose of supply, irrigation, flood control or prevention of droughts. Specifically for mining, tailings dams are the most common form of existing tailings storage. However, associated risks accompany works of this magnitude and possible ruptures of a dam can trigger disasters. Impacts depend on the vulnerability of the environment and society and can drastically affect all locally constituted living elements and can cause loss of social and economic order throughout a mode of population organization. Thus, this study has the objective of conducting an analysis of the vulnerability and risk perception of the Industrial district and Vila do Conde, which are the neighborhoods around the kaolin reject basin nº3 (B3) located in the municipality of Barcarena (PA). To perform this research were used secondary data of the municipality, legislation and the Emergency Action Plan of the dam; and primary data obtained in the field from the use of 143 questionnaires. As results were identified elements that characterize the vulnerability of the populations downstream of the B3 basin, both in Vila do Conde and in the Industrial neighborhood, such as: the proximity of these areas of the B3 basin, family income less than one (1) minimum wage (71.33%), (29.37% do not have complete primary education), 60.14% of the households have at least one (1) child, and 36.73% have elderly and 4.17% with special needs. In this way it is concluded that it is important that there is an intervention of the public power in order to carry out preventive actions with the population, as well as to establish bases for its action in the event of a disaster event in the study area presented here.